Analysis of competitive factors for exports of the Brazilian and Argentine Soybean Complex - Gabbi, Maiara Thaís Tolfo; Costa, Nilson Luiz; Oliveira, Gabriel Nunes de (Revista Economia Ensaios, 2024)
The study aimed to investigate which factors explain the intensification in exports of soybean derivatives by Argentina, and of grains by Brazil. For this, the method of content analysis was used through semi-structured interviews. The results show that the soybean processing segment in Argentina has comparative advantages derived from the concentration of production, industrial plants with high processing capacities, facilitated logistics, tax differential, restricted domestic demand and the collection of royalties. While Brazil intensified grain exports, mainly due to Chinese demand, the imposition of trade barriers on derivatives, tax incentives and long distances.